Hubungan Kecemasan Sosial dengan Pengungkapan Diri dalam Hubungan Pertemanan - Miryam Ariadne Sigarlaki; Ayu Aulia Nurvinkania (Universitas Kristen Maranatha, 2022)
Social anxiety is a condition of an individual who experiences anxiety in a social environment. One of the developmental tasks of late adolescents is to establish mature relationships with peers, where self-disclosure is one of the factors that support the relation to run smoothly. The purpose of this quantitative research is to determine the relationship between social anxiety and self-disclosure among university “X” students. The hypothesis is that there’s a relationship between social anxiety and self-disclosure. The sample used was 106 people. The researcher used the SAS-A (Social Anxiety Scale for Adolescents) by La Greca and Lopez (1998), which was translated into Indonesian by Rizkadina (2016), and the self-disclosure measuring tool made by Miranda (2021) based on Wheeless & Grotz (1976) theory. The results show there’s no significant relationship between social anxiety and self-disclosure. Future research is expected to consider other variables that may have a relationship with both variables.